Implementasi Algoritma Camellia Pada Penyandian Record Database - Neti Rusri Yanti; Taronisokhi Zebua (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
Database records in the form of text are very widely used, so it is very vulnerable to data theft by unauthorized parties. In order to maintain the security of database records, it can be done by using cryptographic techniques. Cryptographic techniques can encode database records by encrypting them in the form of passwords that are not understood. The Camellia algorithm is one algorithm that can be relied upon to realize cryptographic techniques. This symmetry algorithm will produce a higher level of security against the database record because it can encode it into a password with a fairly complex process that will make it difficult for cryptanalysts to access the database. This research will use the 128 bit Camellia algorithm for the encryption and decryption process, so that in the process it is necessary to go through several long steps in order to produce the final cipher. This algorithm requires 18 rounds where every six rounds must enter Function F and Function FL-1 and also require as many as 26 subkeys, namely kw, k and kl. This study describes the process of securing a database record by encoding it based on the Camellia algorithm, so that it produces a text record database in the form of a password that is difficult for others to understand and understand. This is done in an effort to minimize acts of misuse of database records.